2018
DOI: 10.1186/s12902-018-0238-2
|View full text |Cite
|
Sign up to set email alerts
|

An international survey on hypoglycemia among insulin-treated type I and type II diabetes patients: Turkey cohort of the non-interventional IO HAT study

Abstract: BackgroundLimited real-world data are currently available on hypoglycemia in diabetes patients. The International Operations Hypoglycemia Assessment Tool (IO HAT) study was designed to estimate hypoglycemia in insulin-treated type I (T1DM) and type II (T2DM) diabetes mellitus patients from 9 countries. The data from Turkey cohort are presented here.MethodsA non-interventional study to determine the hypoglycemia incidence, retrospectively and prospectively, in Turkish T1DM and T2DM patients using a 2-part self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 18 publications
0
10
1
4
Order By: Relevance
“…The higher magnitude of hypoglycemia in this study might be due to fact that most of the diabetic patients had type 1diabetes and were on insulin. However, the finding of this study was lower than found in recent large prospective studies on self-reported incidence of hypoglycemia in diabetic patients; in which nearly all patients reported hypoglycemia during the prospective period [13, 14]. The higher frequency of hypoglycemia in prospective studies can be explained by recall bias in self-reporting hypoglycemia in retrospect.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…The higher magnitude of hypoglycemia in this study might be due to fact that most of the diabetic patients had type 1diabetes and were on insulin. However, the finding of this study was lower than found in recent large prospective studies on self-reported incidence of hypoglycemia in diabetic patients; in which nearly all patients reported hypoglycemia during the prospective period [13, 14]. The higher frequency of hypoglycemia in prospective studies can be explained by recall bias in self-reporting hypoglycemia in retrospect.…”
Section: Discussioncontrasting
confidence: 89%
“…In the study from Austria, self-reported hypoglycemia rate in type 1 respondents was four times greater than the rates reported by type 2 respondents [22]. Other studies have also shown higher frequency of hypoglycemia in type 1 diabetes when compared to type 2 diabetic patients despite being on similar type of treatment [13, 14, 23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While abdominal wall endometriosis (AWE) can be seen spontaneously, it usually develops secondary to a surgical operation such as a cesarean section (CS), hysterectomy, or laparoscopy [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Emral ve ark. (2018) ülkemizde yaptığı bir çalışmada Tip 1 diyabeti olan hastaların %74'ünün, tip 2 diyabeti olan hastaların ise %53.6'sının hipoglisemi yaşadığı belirlenmiştir (6).…”
Section: Dokuz Eylül üNiversitesi Hemşirelik Fakültesi Elektronik Dergisiunclassified